2015
DOI: 10.1007/s12603-015-0619-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin K on vascular health and physical function in older people with vascular disease–a randomised controlled trial

Abstract: Six months of vitamin K2 supplementation did not improve markers of vascular health or physical function in older patients with vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 32 publications
0
56
1
Order By: Relevance
“…Specifically, the mean difference and SD in VC were calculated from median, IQR and sample size7 using a method described previously 18. SD of VS or VKDP was calculated from mean and 95% CI8 or mean and p value11 17 according to standard methods 19. Percentage effect sizes in VC, VS and ucVKDP were calculated to account for heterogeneity of type and scale of outcome measures.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the mean difference and SD in VC were calculated from median, IQR and sample size7 using a method described previously 18. SD of VS or VKDP was calculated from mean and 95% CI8 or mean and p value11 17 according to standard methods 19. Percentage effect sizes in VC, VS and ucVKDP were calculated to account for heterogeneity of type and scale of outcome measures.…”
Section: Methodsmentioning
confidence: 99%
“…One randomized controlled trial was further excluded as vitamin K, D, and calcium cosupplementation was compared against placebo 40. The remaining nine randomized, placebo-controlled trials29,3037 met the inclusion criteria. However, two papers29,32 were duplicate reports.…”
Section: Resultsmentioning
confidence: 99%
“…However, two papers29,32 were duplicate reports. The paper reporting more complete data32 was included, leaving eight randomized controlled trials in the systematic review and meta-analysis3037 (Figure 1). Of the eight trials, two30,35 enrolled the same group of participants, but reported different outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations